Rooting, Growth, and Root Morphology of the Cuttings of Ficus carica L. (cv. “Dottato”): Cutting Types and Length and Growth Medium Effects - Rocco Mafrica; Marcello Bruno; Vincenzo Fiozzo; Roberta Caridi; Agostino Sorgonà (Plants)
The fig tree (Ficus carica L.) has gained renewed interest for its climate resilience and the health benefits of its fruit, driving demand for high-quality nursery plants. However, suboptimal propagation techniques limit the nursery production of figplants. This study evaluated the influence of the type and length of the cutting and the growth medium on rooting success, biomass yield and allocation, and root morphology in fig plants of the “Dottato” cultivar. Results pointed out that distal and longer cuttings significantly enhanced rooting efficiency and biomass production and allocation, yielding optimal shoot and root morphology for transplanting success. Multivariate analysis identified critical traits differentiating fig nursery plants’ quality across treatments. Additionally, the results showed that favorable outcomes were achieved across various growth mediums. These insights provide practical strategies to optimize propagation techniques and improve plant quality for sustainable fig cultivation.